Functional interrogation of CRISPR-CAS9 mediated EpCAM knockout in breast cancer cells / Afiqah Fasihah Abdul Rahim - Afiqah Fasihah , Abdul Rahim (2022)
Breast cancer is the most common cancer, and it ranks among the top three in terms of new cases. Many factors contribute to the development of breast cancer, including overexpression of particular genes that promote tumourigenesis. EpCAM which encodes for a pro-metastasis protein, has been consistently associated with the developments of many epithelial cancers including breast cancer. This research aimed to determine the role of EpCAM in MCF-7 and T-47D breast cancer cell lines using CRISPR-Cas9 genome editing tool. Also, this study further investigated the phenotypic effects of knockout EpCAM using functional assays that measured cell migration, proliferation, adhesion and colony formation. The CRISPR-Cas9 genome editing approach was found to successfully perturbed EpCAM functions in both breast cancer cell lines. Similarly, observations on the functional assays showed that knocking out EpCAM reduced cell migration, inhibited cell proliferation while reducing the abilities of the cells to form colonies and cell adhesion. These findings indicate that knocking out EpCAM has a tumour suppressor effect, which suggests EpCAM as a potential target in breast cancer therapeutics.